2022
DOI: 10.2147/idr.s365394
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Tuberculosis Treatment Outcome and Associated Factors at the University of Gondar Comprehensive Specialized Hospital: A Ten-Year Retrospective Study

Abstract: Background Multidrug-resistant tuberculosis (MDR-TB) remains a public health crisis and a health security threat worldwide. Poor public health infrastructure, inefficient infection control and mismanagement of TB treatment are among the reasons for the continuous emergence and spread of drug-resistant TB (DR-TB). The final treatment outcome is the most direct measurement of TB control programs. Therefore, this study sought to determine the proportions and predictors of TB treatment outcomes among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
1
8
1
1
Order By: Relevance
“…5,7,8 This age group of young adults (18-30 years) (31.8%) demonstrated unfavorable treatment outcomes which may have certain possibilities like exposed to more infectious pathogens, poor treatment compliance as a result of the lengthy treatment period, and having to forgo high-risk behaviors such as smoking and alcoholism, which weakens the immunity, ultimately led to poor treatment adherence, which has been shown to have negative effects on health, while Belachew et al, from Ethiopia in a 10 year retrospective review, found old age to be significantly associated with unsuccessful treatment outcome. 9 Small sample size in the above cited studies and the present study could be a reason for not getting enough power to demonstrate the effect of age or sex on treatment outcome. 5,7,8 Majority of the DR-TB isolates in this study belong to below poverty line (62.2%), although, showed treatment success rate on higher side, not statistically significant with the treatment outcome, and might be with the reason of timely and adequate implementation of the U-DST to provide accurate diagnostic services and modification of the treatment regimen.…”
Section: Discussionmentioning
confidence: 68%
“…5,7,8 This age group of young adults (18-30 years) (31.8%) demonstrated unfavorable treatment outcomes which may have certain possibilities like exposed to more infectious pathogens, poor treatment compliance as a result of the lengthy treatment period, and having to forgo high-risk behaviors such as smoking and alcoholism, which weakens the immunity, ultimately led to poor treatment adherence, which has been shown to have negative effects on health, while Belachew et al, from Ethiopia in a 10 year retrospective review, found old age to be significantly associated with unsuccessful treatment outcome. 9 Small sample size in the above cited studies and the present study could be a reason for not getting enough power to demonstrate the effect of age or sex on treatment outcome. 5,7,8 Majority of the DR-TB isolates in this study belong to below poverty line (62.2%), although, showed treatment success rate on higher side, not statistically significant with the treatment outcome, and might be with the reason of timely and adequate implementation of the U-DST to provide accurate diagnostic services and modification of the treatment regimen.…”
Section: Discussionmentioning
confidence: 68%
“…The current study found 66.1% of successful treatment outcomes, which is consistent with the studies done in Northwest Ethiopia 63% [33] and Haiti, 66.4% [34] . However, it was lower than the national treatment success rate of 75.7% [35] , 81.1% in Uganda [36] , 76.9% in Addis Ababa [37] and 77.1% in Gonder compressive Specialized Hospital [38] . The difference in the current success rate could be attributed to progress over time, a patient condition during admission, program organization, setting, and a variety of other factors.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the recent improvements in the treatment of multidrug- or rifampicin-resistant and resistant tuberculosis (MDR/RR-TB), not all patients experience treatment success [ 1 , 2 ]. Even among patients receiving all-oral and/or shortened regimens, those living with HIV or advanced TB experience a higher risk of unfavourable treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%